Construction and constriction - Gaglio, Charla Y., author; Lundberg, Thomas R., advisor; Silberberg-Peirce, Susan, committee member; Kneller, Jane, 1954-, committee member; Fahey, Patrick G., committee member (Colorado State University. Libraries, 1999)
To view the abstract, please see the full text of the document.
Keywords: Textile fabrics in art